Anti‐Dioxylation of Cyclohex‐4‐ene‐1, 2‐diamine Derivatives: Asymmetric Routes to Hydroxy‐ and Amino‐Substituted Cyclohexane and 7‐Azanorbornane. Issue 9 (23rd January 2014) - Savoia, Diego; Balestri, Davide; Grilli, Stefano; Monari, Magda
Abstract: The highly diastereoselective anti ‐dioxylation of (1 R, 2 R )‐1, 2‐bis[(1 S )‐phenylethylamino]cyclohexene was accomplished through epoxidation of the double bond with m ‐chloroperbenzoic acid ( m CPBA) in the presence of a sulfonic or trihaloacetic acid and ring opening of the epoxide in situ in the presence of sulfonate or carboxylate anions. The two procedures, after basic quenching and reductive removal of the N‐substituents, provide stereoselective access to 2‐ exo ‐5‐ endo ‐5‐amino‐7‐azabicyclo[2.2.1]heptan‐2‐ol and 4, 5‐diaminocyclohexane‐1, 2‐diol, respectively. The different outcomes are explained by differing chair conformations of the protonated diamine‐epoxide intermediates, which undergo ring opening through a preferred anti ‐diaxial mechanism. Abstract : The outcome of the reactions of N, N ′‐disubstituted trans ‐1, 2‐cyclohex‐4‐enediamine with m ‐chloroperbenzoic acid in acidic medium is dependent on the nature of the acid used, which affects the equilibrium between alternative chair conformers of the intermediate epoxide. A highly stereoselective route to 4, 5‐diaminocyclohexane‐1, 2‐diol and functionalized 7‐azabicyclonorbornane is described.